2022
DOI: 10.1029/2021ea002185
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of Indian Summer Monsoon Synoptic Activity in Response to Polar Sea Ice Melt Induced by Albedo Reduction in a Climate Model

Abstract: The effect of polar sea ice melt on low latitude climate is little known. To understand the response of the Indian summer monsoon (ISM) synoptic activity to the sea ice melt, we have run a suite of coupled and uncoupled climate model simulations. In one set of simulations, the albedo of sea ice is reduced so that it would melt due to increased absorption of solar radiation. The coupled model simulation with a reduced sea ice albedo resulted in an almost complete melting of the sea ice in summer in both hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Each of these runs span for four years, giving a total of sixteen years of data. Similar high-resolution atmospheric model simulations have been performed to investigate the changes in monsoon low-pressure systems (Sandeep et al, 2018;Chandra et al, 2022).…”
Section: Coupled and Uncoupled Climate Model Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each of these runs span for four years, giving a total of sixteen years of data. Similar high-resolution atmospheric model simulations have been performed to investigate the changes in monsoon low-pressure systems (Sandeep et al, 2018;Chandra et al, 2022).…”
Section: Coupled and Uncoupled Climate Model Simulationsmentioning
confidence: 99%
“…The polar sea ice melt can also elicit a climate system response similar to that of global warming (England et al, 2020). Recent studies using coupled models suggest that both Arctic and Antarctic sea ice melt can influence changes in the deep tropics (Liu and Fedorov, 2019;England et al, 2020;Chandra et al, 2022). Using climate model simulations, Chandra et al (2022) showed that the Indian summer monsoon circulation and synoptic activity would weaken in response to the polar sea ice melt.…”
mentioning
confidence: 99%
See 2 more Smart Citations